Polylogue in social media – thematic text structure vs linguistic politeness - Podviazkina, Alena (Papers in Linguistics, 2020)
The aim of the article is to show the thematic structure of the social media polylogue as an indication of linguistic politeness. The article is a contribution to the discussion about the way of understanding linguistic politeness. It assumes that one of the patterns of behaviour that are part of linguistic politeness is the cooperative principle (in Grice’s view). The social media polylogue was analysed in terms of the relationship between linguistic politeness and the thematic structure. The undertaken analyses have shown that comments comprising the polylogue respect the maxim of relevance, while compliance with the subject is achieved as a result of formulating direct and indirect acts of speech. As a result of scrutinising reactions to a manifest deviation from the subject, it has been found that the interpretation consisting in connecting the deviation from the maxim of relevance to the problem of linguistic politeness is possible, but requires further studies.